Oral Verruciform Xanthoma: A Case Report and Literature Review - Yonara Maria Freire Soares Marques; Cleverton Roberto de Andrade; Suzana Cantanhede Orsini Machado de Sousa; Cláudia Maria Navarro (Case Reports in Pathology)
Oral verruciform xanthoma represents an uncommon entity, which affects mainly oral mucosa. This paper presents the major clinical and histological features of oral verruciform xanthoma and reports a case on the tongue. The differential diagnosis and a literature review are also provided in light of recent information.